New accountant job market reform by computer algorithm: an experimental study - Hirose, Yoshitaka (2017)
The purpose of this study is to examine the matching of new accountants with accounting firms in Japan.A notable feature of the present study is that it brings a computer algorithm to the job-hiring task.Job recruitment activities for new accountants in Japan are one-time, shortterm struggles.Accordingly, many have searched for new rules to replace the current ones of the process. Job recruitment activities for new accountants in Japan change every year.This study proposes modifying these job recruitment activities by combining computer and human efforts.Furthermore, the study formulates the job recruitment activities by using a model and conducting experiments.As a result, the Deferred Acceptance (DA) algorithm derives a high truth-telling percentage, a stable matching percentage, and greater efficiency compared with the previous approach.This suggests the potential of the Deferred Acceptance algorithm as a replacement for current approaches.In terms of accurate percentage and stability, the DA algorithm is superior to the current methods and should be adopted.